2008
DOI: 10.1038/npp.2008.212
|View full text |Cite
|
Sign up to set email alerts
|

Antiamnesic and Neuroprotective Effects of the Aminotetrahydrofuran Derivative ANAVEX1-41 Against Amyloid β25–35-Induced Toxicity in Mice

Abstract: The antiamnesic and neuroprotective activities of the new aminotetrahydrofuran derivative tetrahydro-N,N-dimethyl-5,5-diphenyl-3-furanmethanamine hydrochloride (ANAVEX1-41), a nonselective muscarinic receptor ligand and s 1 protein activator, were examined in mice injected intracerebroventricularly with amyloid b [25][26][27][28][29][30][31][32][33][34][35] ) peptide (9 nmol). Ab 25-35 impaired significantly spontaneous alternation performance, a spatial working memory, and passive avoidance response. When A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 50 publications
5
85
1
Order By: Relevance
“…At 1 week after injection, A␤ [25][26][27][28][29][30][31][32][33][34][35] induced significant oxidative stress in the hippocampus, as reflected by measured increases in lipid peroxidation, protein nitration, and superoxide generation. [11][12][13]40 In the present study, the early increases in lipid peroxidation levels observed after peptide injection were gradually reduced, particularly in the rat frontal cortex and amygdala, suggesting that oxidative stress could be alleviated by endogenous protective systems (putatively neurotrophins, such as BDNF).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…At 1 week after injection, A␤ [25][26][27][28][29][30][31][32][33][34][35] induced significant oxidative stress in the hippocampus, as reflected by measured increases in lipid peroxidation, protein nitration, and superoxide generation. [11][12][13]40 In the present study, the early increases in lipid peroxidation levels observed after peptide injection were gradually reduced, particularly in the rat frontal cortex and amygdala, suggesting that oxidative stress could be alleviated by endogenous protective systems (putatively neurotrophins, such as BDNF).…”
Section: Discussionsupporting
confidence: 52%
“…9 and 10) and after 1 week in mouse. 11 The extent of cell loss was limited to a 30% to 40% decrease in the number of viable cells in the most vulnerable areas, whereas a significantly greater loss was noted in all pyramidal cell layers. The neurodegenerative process thus appeared to be generalized, contrary to what is usually observed in excitotoxic or chemical neurotoxicity models.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Modifying s 1 protein activation using effective agonists therefore mediates a unique pharmacological action on Ca 2 þ homeostasis and signal transduction pathways, with major impacts on cellular response and plasticity. The idea of developing mixed s 1 /muscarinic ligands was therefore based on the capability to simultaneously activate a neuroprotective pathway, eg, the M1/PLC/PKC pathway, and amplify it, through a concomitant activation of the s 1 protein (Vamvakides, 2002a, b;Espallergues et al, 2007;Villard et al, 2009Villard et al, , 2011. Tetrahydro-N,N-dimethyl-2,2-diphenyl-3-furanmethanamine hydrochloride (ANAVEX2-73) presents such a mixed s 1 /muscarinic receptor profile, with a moderate affinity range.…”
Section: Introductionmentioning
confidence: 99%